ENSAIO CLÍNICO ALEATORIZADO SOBRE O EFEITO DO BISEL NA RETENÇÃO DE RESTAURAÇÕES EM LESÕES CERVICAIS NÃO CARIOSAS - Costa, Thays Regina Ferreira da (2012)
Laboratory testing of enamel bevel showed many advantages such as: reduced leakage, improved aesthetics, reduction of fracture of the enamel, better adhesion to the tooth restoration and others. However, clinical studies about the effect of bevel are scarce and controversial. Due to this, the authors evaluated the effect of the margin configuration on the clinical performance of resin-based composite restorations in Class V non-carious cavities. A total of 42 patients with good general health, more than 20 teeth in occlusion and having at least two non-carious cervical lesions were enrolled in this study. A total of 84 restorations were placed and evaluated at baseline, six, and 12 months of clinical service according to the modified U.S. Public Health Service criteria (retention, marginal adaptation, recurrent decay, post operative sensitivity, marginal discoloration). The cavities were randomly divided into two groups: non bevel (control group) and bevel (where a short bevel was prepared with a diamond bur). The same resin-based composite and adhesive system (Excite and 4 Seasons, Ivoclar Vivadent) were used for all restorations. The 12 months retention rates for the bevel and control group, respectively, were 91 and 88 % and no significant difference were detected between them in all evaluated criteria (Fisher test, p > 0.05). Also no significant differences were detected in the different times of the same group (baseline vs. 6 months; baseline vs. 12 months; 6 months vs. 12 months) - McNemar test, p > 0.05. Enamel beveling seems not to be important for the retention of Class V composite restorations and others criteria after 12 months of clinical service with these materials used.